A systematic review of the relation between ten potential occupational sensitizing exposures and asthma - Dalbøge, Annett; Kolstad, Henrik A.; Jahn, Alexander; Ulrik, Charlotte Suppli; Sherson, David Lee; Meyer, Harald William; Ebbehøj, Niels; Sigsgaard, Torben; Baur, Xaver; Schlünssen, Vivi (Scandinavian Journal of Work, Environment & Health, 2025)
' ' OBJECTIVE ': 'The aim of this systematic review was to identify, evaluate, and synthesize the relation between ten potential occupational sensitizing exposure groups and asthma. ' ' METHODS ': 'A systematic literature search was conducted in three databases for peer-reviewed articles published between July 2011 and March 2023. Exposures included ten potential occupational sensitizing exposure groups (amines, anhydrides, biocides [eg, pesticides], crustaceans, enzymes, mammals, metals, “mold, fungi and yeast”, molluscs, and other chemicals [eg, cleaning agents]) classified as having no or limited evidence of a causal relation with asthma in our previous overview of systematic reviews. We included observational and case studies. Study selection, data extraction, risk of bias assessment, and evidence level evaluation were conducted independently by two reviewers, who also upgraded or downgraded the level of evidence found in our overview. ' ' RESULTS ': 'This review included 55 articles. The overall confidence in study results was rated high in 8, moderate in 18, and low in 29 studies. No new studies were found for molluscs. For the remaining exposures, we upgraded main groups of crustaceans and enzymes to moderate evidence, mammals and metals to limited/contradictory, and amines and biocides to very limited/contradictory. For subgroups/specific exposures, pesticides, cleaning agents – such as chloramine and disinfection products – and an unspecified group of other chemicals, specifically acrylates and epoxy, were upgraded to moderate. ' ' CONCLUSION ': 'New occupational sensitizing exposures with moderate evidence include crustaceans, enzymes, pesticides, cleaning agents such as chloramine and disinfection products, and chemicals such as acrylates and epoxy.
Keywords: allergen; allergy; asthma; exposure; lung disease; occupational sensitizing exposure; respiratory symptom; review; sensitizing exposure; systematic review; work